COMPOSITION OF LYMPHOCYTE SUBSETS IN THE PATIENTS WITH SEVERE FORMS OF HERPETIC INFECTION - I. A. Novikova; M. V. Zlotnikova (Медицинская иммунология, 2014)
Evaluation of lymphocyte subsets in severe forms of herpetic infection is a necessary diagnostic test. However, interpretation of appropriate data is difficult, due to slight or multidirectional changes of immunological parameters in the patients. In present study, the indices of immune status were assessed in the patients with severe recurrent forms of chronic herpetic infection, being in remission period by the time of study. A detailed personalized analysis of immunological testing data is presented, with respect to the disease duration, recurrence frequency, and other clinical features of severe herpes infection. Various types of correlations between the lymphocyte subpopulations are described for the patients with severe recurrent herpetic infection.